UTOPIAN WRITING AND CRITICISM POLICY-AESTHETIC: OF CHURATA TO COLCHADO - Huaman Villavicencio, Miguel Angel (2006)
This paper considers litterature as literacy. Modero culture supports litteraturebecause it contributes to its own legitimation. The reactions to thisphenomenon are different. They depend on the identity of each subject: theone who belongs to the hegemonic culture and ihe other, who sufres thedomination. Both perspectives are the beginning of an analisys that reviewsthe process of peruvian narrative, discovers the writting crisis andits rationality, but, at the same time, reveals the rasing of an utopic writtingof cultural resistance to the impositions of postmodemity.